Spectrophotometric determination of Methyldopa in pure form and in the pharmaceutical preparations - Naji Rashid, Qabas; Hamza Bakir, Mohsin; Omar Baban, Shirwan (Tikrit Journal of Pharmaceutical Sciences, 2023)
A simple, rapid and sensitive spectrophotometric method for determination of methyldopa (MD) using 4-chloro-7-nitrobenzo-2-oxa-1, 3-diazole (NBD-Cl) as reagent in an alkaline medium (pH 12.3). Absorbance of the resulting brown-colored product is measured at 470 nm. Beer’s Law is obeyed in a concentration range of (1.6-17.6 µg/mL) with molar absorptivity (1.9337×104 L/mol.cm), correlation coefficient 0.9988, and the limit of detection (5.536×10-3 µg/mL). The method has been successfully applied to the determination of Methyldopa in pharmaceutical preparations.